Grundtvig og Geijer - Pedersen, Kim Arne (Grundtvig-studier, 1996)
Grundtvig and Geijer - Two Meetings and a Parting By Kim Arne Pedersen The point of departure of the article is partly a seminar, held in the spring of 1996 at Karlstad H.gskola, entitled Grundtvig, Geijer and Their Impact, partly the fact that this year it is 150 years since the first real meeting between Grundtvig and the Swedish historian, Erik Gustav Geijer, took place. This meeting came about in connection with the celebration of Geijer in Copenhagen in 1846. Prior to the personal meeting between the two, Geijer had attended Grundtvig’s church service in Our Saviour’s Church in Christianshavn in 1825.The article begins with a description of similarities and differences between Grundtvig and Geijer. Among other things, the similarities consist in the inspiration from Romanticism, shared by both of them, their emphasis on the Nordic tradition of freedom, and their meeting, in both cases, with the freedom224 loving England. Whereas Grundtvig became isolated in his early years, among other things because he dissociated himself from German Idealism, Geijer never broke with that Idealism, and only late did he experience an isolation from his former conservative-romantic environment. It was precisely in the years when Grundtvig’s isolation is broken that Geijer embraces the ideas of liberty (1838). The article goes on to present Geijer’s desciption of Grundtvig’s church service in 1825. Geijer likes Grundtvig’s sermon, but does not care much for his unmusical chanting of the Mass or the Danish church service customs. The article contains two further references to Grundtvig’s chanting.The article then reproduces two draughts for toast speeches to Geijer, given by Grundtvig in connection with the celebration in 1846, followed by an analysis of the speeches.In the first draught Grundtvig points out that he and Geijer were bom in the same year. In that connection Grundtvig mentions that the movements towards national liberty at the end of the 18th century found a peaceful reflection in Scandinavia. He proceeds to describe the historical interest common to himself and Geijer and sees their appraisal of the North as an indication of the flourishing Nordic life that Grundtvig expects.The other draught begins with Grundtvig’s version of the Greek poet Pindar. He uses Pindar’s poem as an image of the link between Ancient Greek and Nordic culture that he sees as his goal, and he makes it clear that the North today surpasses Greece.In conclusion, the article refers to the last hours of Grundtvig’s life when Geijer’s .Svenska Folkets Historia. was read aloud to him.